PENGARUH DEBT TO EQUITY RATIO, PRICE EARNING RATIO, EARNING PER SHARE, PRICE TO BOOK VALUE TERHADAP RETURN SAHAM SELAMA MASA PANDEMI COVID-19 (STUDI PADA PERUSAHAAN YANG AKTIF TERDAFTAR DALAM LQ45 TAHUN 2019-2021) - Mayasari, Desy; Syaipudin, Usep (Universitas Multimedia Nusantara, 2023)
Abstract” The existence of Covid-19 caused the economy in Indonesia to become unstable, this caused the performance of the LQ45 stock index to experience a decline. This study's goal was to examine how financial ratios affected stock returns during the Covid-19 pandemic. The population of this study is the LQ45 Index which is found on the Indonesia Stock Exchange in 2019-2021 with a total of 54 companies. The samples used were 25 companies selected using purposive sampling method. This study uses secondary data obtained from annual reports published on the official website of the Indonesia Stock Exchange and the company's official website. Data analysis techniques use descriptive statistics and panel data regression. The results of this study indicate that the Debt to equity ratio (DER) and price earning ratio (PER) partially have no effect on stock returns. Meanwhile, earnings per share (EPS) and price to book value (PBV) have a positive effect on stock returns. Simultaneous test results show that the Debt to equity ratio (DER), price earning ratio (PER), earnings per share (EPS) and price to book value (PBV) have a positive effect on stock returns. Keywords: Debt to Equity Ratio (DER); Earnings per Share (EPS); Price Earning Ratio (PER); Price to Book Value (PBV); Stock Returns